Prolonged Transcription in a Cell-Free System Involving Nuclei and Cytoplasm - Wu, Guang-Jer (1974)
A cell-free system for nuclear-directed transcription has been developed that gives prolonged synthesis in the presence of cytoplasm. The nuclear and cytoplasmic components have been prepared from Krebs II ascites tumor cells for most experiments but further observations indicate that components prepared from other cell types may be used. After an initial 5- to 10-min period of relatively rapid RNA synthesis a linear rate ensues for 2-3 hr. In the absence of cytoplasm no net RNA synthesis occurs after the initial 10-min period. Experiments with α-amanitin suggest that about half of the cell-free synthesized RNA is made by RNA polymerase II, the enzyme believed to be responsible for messenger synthesis in vivo. The conditions used for RNA synthesis were derived from conditions found to be optimal for protein synthesis that proceeds linearly for 2-3 hr. It has not yet been possible to demonstrate the synthesis of protein from cell-free synthesized RNA in this system. A major problem here is that isolated nuclei, even when carefully washed, contain a great deal of translatable RNA.